SELF-REGULATED LEARNING SEBAGAI FAKTOR PENTING DALAM MENINGKATKAN MOTIVASI DAN KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR - Nanik Ardhiani, Gusti Ayu; Erna Muliastrini, Ni Ketut (Adi Widya: Jurnal Pendidikan Dasar, 2026)
Abstract This study aims to analyze the role of self-regulated learning in improving learning motivation and independent learning among elementary school students. This research employed a systematic literature review (SLR) approach using a qualitative descriptive method to examine studies related to self-regulated learning, learning motivation, and independent learning. Data sources were obtained from accredited national journals and international journals published between 2020 and 2025 through academic databases such as Google Scholar, Scopus, and Science Direct. Data analysis was conducted through identification, selection, and synthesis of research findings relevant to the research topic. The results indicate that self-regulated learning plays an important role in enhancing students’ learning motivation through the ability to plan learning goals, monitor learning progress, and evaluate learning outcomes independently. Self-regulation skills also contribute to the development of students’ independent learning, reflected in their ability to manage study time, complete learning tasks independently, and take initiative in seeking additional learning resources. These findings suggest that the development of self-regulated learning in the learning process can encourage students to become more active, independent, and responsible learners. Therefore, learning strategies that support the development of self-regulation should be emphasized in elementary school education. Keywords: self-regulated learning, learning motivation, independent learning